Norovirus genogroups I and II in environmental water samples from Bel?m city, Northern Brazil - Teixeira, Dielle Monteiro (IWA Publishing, 2017)
This study investigated the presence of norovirus (NoV) GI and GII in environmental samples from the northern region of Brazil. Water samples were collected monthly (November 2008/October 2010) from different sources and sewage and concentrated by the adsorption-elution method. The NoV investigation used molecular methods followed by sequencing reactions. The general positivity for NoV was 33.9% (57/168). Considering the results obtained only in the semi-nested RT-PCR (reverse transcription polymerase chain reaction) and only in the TaqMan? real-time PCR, the rates were 26.8% (45/168) and 27.4% (46/168), respectively, being for NoV GI 22.2% (10/45) and 19.6% (9/46); for GII 17.8% (8/45) and 15.2% (7/46); and for GI + GII 60% (27/45) and 65.2% (30/46), respectively. Different GI (GI.1, GI.4, GI.7 and GI.8) and GII (GII.4, GII.6, GII.9, GII.12 and GII.14) genotypes were detected. These results demonstrated the NoV was disseminated in the waters of Bel?m city due to a lack of sanitation that allowed the discharge of contaminated effluents into these aquatic ecosystems.